JURIDICAL REVIEW ARTICLE 27A OF LAW NUMBER 1 OF 2024 CONCERNING THE SECOND AMENDMENT TO LAW NUMBER 11 OF 2008 CONCERNING INFORMATION AND ELECTRONIC TRANSACTIONS - Muzakkir; Taufik Hidayat (Fakultas Hukum, Universitas Samudra, 2024)
Nowadays, the rapid development of communication through the internet has also led to various crimes committed using the internet media. The purpose of this research is to find out the differences in the offence of insult and/or defamation contained in the Criminal Code and those contained in Law number 1 of 2024 concerning the Second Amendment to Law number 11 of 2008 concerning Electronic Information and Transactions (UU ITE). This research uses normative juridical research methods, namely legal research that prioritises a library approach (library research). That the difference in offence and defamation contained in the Criminal Code and the ITE Law is between defamation or offence contained in Article 310 of the Criminal Code and Article 27A jo. Article 45 paragraph (4) of the ITE Law is that in Article 310 of the Criminal Code, the element of an act that attacks honour or good name is an act that tells or damages the good name or dignity of another person that is done directly by means of oral or written to inform the public, while in the ITE Law, the act of damaging honour or good name is an act that damages or damages the good name or dignity of another person that is done in the form of electronic information and/or electronic documents carried out through an electronic system. The juridical review of Article 27A of the ITE Law is that the act of attacking the honour or good name of another person is carried out in the form of electronic information and/or electronic documents carried out through an electronic system.